2016
DOI: 10.1016/j.cirpj.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transparent objects metrology through diamond cutting edge radii measurements

Abstract: The efficiency of cutting is largely influenced by cutting edge radii. When considering the correct cutting edge radius in the simulations, correct cutting characteristics can be predicted and thus the cutting process optimized. Sharpening the cutting edge of the tool to a specific optimized radius subsequently will improve the service life of the tool, workpiece quality, and performance of cutting. Measuring cutting edge radii of tools already is challenging, especially when measuring cutting edge radii of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Maximum prediction error is 9.5 % for the cutting force and 5.9 % for the normal force. This 9.5 % deviation between simulation and experiment can be explained by considering the uncertainties in experimental results as explained in [17]. Compared with other works [5,6,9], the results are of considerable accuracy.…”
Section: Process Forcesmentioning
confidence: 79%
“…Maximum prediction error is 9.5 % for the cutting force and 5.9 % for the normal force. This 9.5 % deviation between simulation and experiment can be explained by considering the uncertainties in experimental results as explained in [17]. Compared with other works [5,6,9], the results are of considerable accuracy.…”
Section: Process Forcesmentioning
confidence: 79%
“…Given experimental conditions where the tool is in full contact with the workpiece and the cutting forces reach steady state, the three components of the cutting forces were validated with experiment for a damage limit of 0.7. Also as proved by (Akbari et al, 2016), the diamond grains have different cutting edge radii and it is important to understand the role of different cutting edge radii in simulation of machining. It is found that in machining with large negative rake angles, cutting and passive forces were reduced with sharper cutting edges.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure is necessary to overcome the problems of meshing the diamond. Then based on (Akbari et al, 2016) cutting edge radius of 7 µm is considered for the diamonds.…”
Section: Determination Of Diamond Grain Shapementioning
confidence: 99%
See 2 more Smart Citations